2006
DOI: 10.1159/000096128
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology of Spinal Muscular Atrophy Type I in Estonia

Abstract: Spinal muscular atrophy is the second most frequent autosomal-recessive disorder in Europeans. There are no published epidemiological data on SMA in Estonia and other Baltic countries. The aim of this study was to estimate the incidence of SMA I in Estonia. All patients with SMA I diagnosed between January 1994 and December 2003 were included in the study. The diagnosis was established on the basis of neurological evaluation, ENMG findings, molecular studies and muscle biopsy. PCR and restriction enzyme analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
(31 reference statements)
0
4
0
1
Order By: Relevance
“…The calculations are also based on small patient populations. Nonetheless, the number of patients diagnosed genetically is generally comparable or even higher than reported in previous epidemiological studies [1317], at least in countries, where genetic testing is readily available.…”
Section: Discussionmentioning
confidence: 50%
“…The calculations are also based on small patient populations. Nonetheless, the number of patients diagnosed genetically is generally comparable or even higher than reported in previous epidemiological studies [1317], at least in countries, where genetic testing is readily available.…”
Section: Discussionmentioning
confidence: 50%
“…In Estonia, the birth prevalence of genetically confirmed SMA has previously been reported in a smaller cohort (15 patients) between the years 1994–2003 as 1:8,655 ( Vaidla et al, 2006 ). The present study shows similar results (1:8,286), which indicates that our diagnostic efficacy has stayed on the same level.…”
Section: Discussionmentioning
confidence: 91%
“…Although SMA type I is expected to account for more than half of all new SMA cases [30], the studies that examined a SMA type I only showed a prevalence of 0.04 to 0.28 per 100,000 [24, 25, 3134], which is much lower than the 1–2 per 100,000 persons noted for all SMA. Due to its severity, patients with SMA type I have a short life expectancy.…”
Section: Prevalence and Incidence Of Smamentioning
confidence: 99%